ANALISIS PELUANG DERET HARI KERING PADA TANAMAN PADI TADAH HUJAN DI KABUPATEN KULONPROGO DALAM PERSPEKTIF TOPOSEKUENS (PROBABILITY ANALYSIS OF DRY SPELL ON RAINFED PADDY AT KULON PROGO DISTRICT IN TOPOSEQUENCE PERSPECTIVE) - F. Fibrianty; S. Sarjiman (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2006)
Climate anomaly has significant impact on rainfall and its pattern, whereas they were important factor in determining onset of wet and dry season. Changes in rainfall pattern need to antisipate with tailoring planting date for minimize harvest risk. This research purpose to analyse dry spell probability and its relation to drought risk on rainfed paddy at Kulon Progo District in Toposequence Perspective.Kulon Progo District was divided into three sequence, that were Fluvial as catchment area (i.e. Samigaluh); Freatik as conservation area (i.e. Kenteng, Kalibawang and Kokap); and Fluksial as user area (i.e. Gembongan- Sentolo, Sapon-Lendah and Wates). The aimed of this research was to analyze the drought periods and its relation with drought risks on rainfed rice plant at Kulon Progo district in toposequence perspective. The probabilities of 15 day dry spell at Fluvial area were 0,27 – 0,44 on May-September. On Freatik area, the probabilities of 15 day dry spell were 0,21 - 0,43 on April-Oktober at Kenteng, while at Kalibawang and Kokap the probabilities were > 0,2 on May-September. The probabilities at Gembongan-Sapon were> 0,2 on May-October, while at Wates the probabilities on May-September were 0,21-0,32. The distribution of probability show that the probability of 15 day dry spell were > 0,2 at May-October and the driest periods were August-September but with various dry level, that Kenteng and Gembongan-Sapon were the driest area. Based on that analysis, the planting periods should be started on November and the last planting should not over than January, especially at Kenteng, Gembongan and Sapon.